The impact of implementing environmental management accounting (EMA) on the financial performance of manufacturing firms in Davao City - Medina, Leopoldo D. (Animo Repository, 2003)
This study determines the impact of implementing environmental management accounting (EMA) on the financial performance of manufacturing firms in Davao City. Financial performance is measured in terms of return on equity (ROE) and return on assets (ROA) while EMA implementation is measured in terms of the extent of applying the EMA components namely: environmental cost assessment, tracking of material flows, use of process flow charts, use of activity-based costing, use of total cost assessment and use of pollution prevention techniques. The basis of selecting these components is the EMA procedures and principles developed by the United Nationsl Division for Sustainable Development. A total of 48 companies were surveyed and their audited financial statements were obtained from the Securities and Exchange Commission (SEC). Data analysis included simple frequency table for company profile, weighted means for extent of EMA implementation, and correlation analyses for determining whether a significant relationship exists between EMA implementation and financial performance. Based on the research findings, EMA was extensively implemented by the manufacturing companies in Davao City. However, all EMA applications have negligible relationship with the ROE and ROA. The high p-values indicate that the correlation coefficients are not significant, which means that they do not contribute any evidence that a relationship exists between EMA implementation and financial performance. It can be concluded that savings brought about by eliminating waste and improving efficiency were not significant to attain a considerable improvement in the profitability of local companies over the last two years. EMA's benefits could not be easily translated to profits if companies have not fully embraced EMA. The cost entailed in fully adopting EMA is not cheap. Improvement of information systems to capture the full spectrum of environmental costs would necessitate substantial resources. It may take some time to reap the financial rewards.